Endoscopic Treatment of Rathke’s Cleft Cysts: The Case for Simple Fenestration - Matthias Millesi; Carolyn Lai; Ruth Lau; Vincent Chen Ye; Kaiyun Yang; Matheus Leite; Nilesh Mohan; Ozgur Mete; Shereen Ezzat; Fred Gentili; Gelareh Zadeh; Aristotelis Kalyvas (Brain Sciences, 2022)
Background: Rathke’s cleft cysts (RCC) arise from the pars intermedia because of incomplete regression of the embryologic Rathke pouch. A subset of RCC becomes symptomatic causing headaches, visual and endocrinological disturbances such that surgical intervention is indicated. Several points in surgical management remain controversial including operative strategy (simple fenestration (SF) vs complete cyst wall resection (CWR)) as well as reconstructive techniques. Methods: A retrospective analysis was conducted of pathologically confirmed RCC operated on by endoscopic endonasal approach from 2006 to 2019. Pre-operative symptoms, imaging characteristics, operative strategy, symptom response, complications and recurrences were recorded. Results: Thirty-nine patients were identified. Thirty-three underwent SF and six underwent CWR. Worsening pituitary function was significantly increased with CWR (50%) compared to SF (3%) (p = 0.008). All patients underwent “closed” reconstruction with a post-operative CSF leak rate of 5% (3% SF vs 16% CWR, p = 0.287). Six (15%) recurrences necessitating surgery were reported. Recurrence rates stratified by surgical technique (18% SF vs 0% CWR, p = 0.564) were not found to be significantly different. Conclusions: The current series illustrates variability in the surgical management of RCCs. SF with closed reconstruction is a reasonable operative strategy for most symptomatic RCCs cases while CWR can be reserved for selected cases.